Fragmentary thinking and Psychology in Henri Bergson - Camolezi, Marcos Daniel (Primeiros Escritos, 2009)
This article aims at studying some psychological reflections of the Essay on the Immediate Data of Consciousness. First, it is important to make a critique of mechanicism and associationism in order to comprehend their intellectual modus operandi, recognizing that mental reality escapes from all intelligent procedures: only the intuition can apprehend the psychological modus vivendi. The intuitive comprehension of Time without Space is thus the key for a psychology that aims at establishing a close contact with the subjective interiority. In this context Alberto Caeiro might be regarded as a poet who is also contrary to the fragmental and spatial thinking